Altered states: changing conditions of excess in European drinking cultures - Dias-Lewandowska, Dorota (Routledge handbook of intoxicants and intoxication, 2023)
This chapter provides a historically and culturally comparative perspective on the socially contested boundary between excess and moderation in relation to alcohol by drawing on four distinct, yet complementary, cases. Beginning with late medieval and early modern Western Europe and sixteenth- to nineteenth-century Poland, and then turning to twentieth-century and contemporary Britain, the chapter explores how various religious, state and cultural authorities have sought to define excessive and moderate drinking, and how a diverse set of actors has negotiated their drinking in relation to these textual and visual discourses. As such, the chapter considers the continual interplay between the definition, regulation and practice of excess in a range of contexts, identifying how definitions, regulations and practices of excess exist in a state of changing reciprocation, and reinscription over time; the case studies illustrate how as the perception of excess drives regulation, these regulatory efforts themselves can serve to produce and invite excess. Further, the authors argue that contradictions and double standards abound in authorities’ efforts to construct the boundary between excess and moderation in each instance under study, suggesting that one of the consistent contentions over the definition of excess is this inconsistency. The chapter is the product of an interdisciplinary approach that brings together the conversant disciplines of history, sociology, anthropology and communications studies. This interdisciplinarity is itself reflective of the discussions and specialisms of the Drinking Studies Network Excess Cluster, out of which the chapter developed. Though broad in its temporal and cultural focus, the chapter benefits from a considerable degree of productive thematic and analytical overlap as a consequence of its collaborative origins, offering insight into a heterogeneous field of study. As the chapter makes clear, there is no singular definition of what constitutes ‘excess’, nor is there a form of regulation consistent across the temporal span and cultural contexts that it covers; in the chapter’s final analysis, what becomes apparent in these studies is the semantic fluidity of the notion of excess, which may turn from a social norm into undesirable behaviour, with the simultaneous evolution of the very concept of excess itself.